Formation Features of the Porous Silicon Layers Modified by НСl and HBr in the Context of Optical Properties - Е.I. Zubko (Журнал нано- та електронної фізики)
Transmission and reflection spectra, refraction factor of the porous silicon layers produced in HF(48%): HCl:H2O and HF(48%):HBr:H2O solutions are investigated by the sample illumination and without it. It is established that layers produced by electrolytic anodizing in HF(48%):HBr:H2O = 16:2:80 mass% solution have the best antireflective characteristics and smaller optical transmission than other samples.